Technology of Obtaining Two-Layer Knitted Fabrics in a New Structure of a Flat TwoNeedle Knitting Machine with the Needles Placed in a Rubber Arrangement (Global Scientific Review, 2023)
Using the technological capabilities of modern double bed flat knitting machines, the technology for producing double-layer knitted fabrics of a new structure, made by arranging the needles in rib positions, has been studied.